Application of Several Doses of Dolomite and Pearl NPK on the Growth and Yield of Groundnut (Arachis hypogaea L.) - Nova Lestari, Diana; Adnan; Mardia Apriansi; Eko Fransisko (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2023)
Peanut productivity in Bengkulu Province in 2021 is 2,498 tonnes/ha. However, the productivity of peanuts is still low compared to the average national productivity, which has an average production of around 3,595 tonnes/ha. Soil fertility is an important factor for farming. For this reason, it is necessary to take appropriate actions, one of which is to improve soil nutrients, one of the actions taken is liming the soil. Apart from that, fertilization is also important to note in increasing peanut production by using pearl NPK doses. Pearl NPK is one of the inorganic fertilizers. This study aims to determine the best dosage of dolomite and pearl NPK fertilizer on the growth and yield of peanuts. This study used a randomized block design (RBD) using 2 treatment factors with 4 levels and 4 repetitions, each repetition consisting of 4 plants. Then 16 combinations were obtained, with the total plants used, namely: D×N×T×U= 4×4×4×3= 192. The data obtained were analyzed using ANOVA and continued with 5% DMRT. The results showed that the dose of dolomite was 200 grams and 50 gram pearl NPK fertilizer has an effect on the observed variables, namely plant height, number of leaves, number of flower strands, number of pods, wet weight, and dry weight. Based on the results of ANOVA, it can be concluded that dolomite has an effect on the growth and yield of peanuts, NPK pearl fertilizer treatment has an effect on the growth and yield of peanuts, the interaction of dolomite and NPK pearl fertilizer has an effect on the growth and yield of peanuts.